(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The article analyzes modern legal reforms and priority areas of state policy regarding the protection of women’s and children’s rights in Uzbekistan. It examines gender equality, anti-violence measures, the protection order system, and socio-legal assistance for victims based on statistical analysis and new legal frameworks.